Social cognitive development and childhood tales: tools for teaching - Rodrigues, Marisa Cosenza; Tavares, Aline Lima (Paidéia (Ribeirão Preto), 2009)
This study aimed to evaluate the occurrence of mental terms in a sample of Brazilian children's books and the possibility to explore narratives through the process of the social information model. Based on international studies, 119 Brazilian books directed to preschoolers were analyzed considering four axes: (a) words and expressions denoting mental states; (b) convergence figure/mental state; (c) situational irony and false belief and (d) situations giving social tips. The results indicate a high number of references to mental states (99%), with predominance of cognitive (42%) and emotional terms (39%), high convergence figure/mental state (74%), presence of irony (21%) and false belief (13,5%), and expressive occurrence of situations involving internal and external social tips (98%). The use of children's books as a resource to promote social-cognitive development is discussed and support is presented with a view to contribute to the practice of preschool teachers.